CuO supportd Ce-Ti mixed oxides for low-temperature SCR of NO with propene - Liu, J.; Li, Xin Yong; Zhao, Q.; Zhang, D. (2012)
CuO/TiO 2, CuO/Ti 0.9Ce 0.1O 2 and CuO/CeO 2/TiO 2 composite catalysts were prepared and tested for their application in selective catalytic reduction (SCR) of NO with C 3H 6. The effect of CeO 2 species on the catalytic performance was further evaluated. Catalyst characterization including BET surface area, XRD and temperature-programmed reduction of H 2 (H 2-TPR) suggested that the addition of CeO 2 species changed the physicochemical properties of the catalysts obtained. Compared to the impregnation method, the homogeneous precipitation method was an effective approach to preparing the CeO 2 doped catalyst, which could promote the activation of C 3H 6 to react with NO.